A decade of coral biobanking science in Australia - transitioning into applied reef restoration - Hobbs, Rebecca J.; O'Brien, Justine K.; Bay, Line K.; Severati, Andrea; Spindler, Rebecca; Henley, E. Michael; Quigley, Kate M.; Randall, Carly J.; van Oppen, Madeleine J. H.; Carter, Virginia; Zuchowicz, Nikolas; Hagedorn, Mary; et al. (Frontiers in Marine Science, 2022)
Active restoration or intervention programs will be required in the future to support the resilience and adaptation of coral reef ecosystems in the face of climate change. Selective propagation of corals ex situ can help conserve keystone species and the ecosystems they underpin; cross-disciplinary research and communication between science and industry are essential to this success. Zoos and aquaria have a long history of managing ex situ breed-for-release programs and have led the establishment of wildlife biobanks (collections of cryopreserved living cells) along with the development of associated reproductive technologies for their application to wildlife conservation. Taronga Conservation Society Australia’s CryoDiversity Bank includes cryopreserved coral sperm from the Great Barrier Reef, which represents the largest repository from any reef system around the globe. This paper presents results from an inventory review of the current collection. The review highlighted the skew toward five Acropora species and the necessity to increase the taxonomic diversity of the collection. It also highlighted the need to increase geographic representation, even for the most well represented species. The inventory data will inform Taronga’s future research focus and sampling strategy to maximize genetic variation and biodiversity within the biobank and provide a test case for other practitioners implementing biobanking strategies for coral conservation around the world. Through co-investment and collaboration with research partners over the next decade, Taronga will prioritize and resource critical applied research and expand biobanking efforts to assist interventions for reef recovery and restoration.